Checklist of Hinton's collections of the flora of south‑central Nuevo Leon and adjacent Coahuila - Hinton, James; Hinton, George S. (Instituto de Ecología, A.C., 1995)
A preliminary checklist of the flora of south-central Nuevo León and part of adjacent Coahuila includes 1955 species, in 713 genera and 130 families. At least 200 species, an estimated 10 percent of the total flora, are endemic to this area, mostly on exposed gypsum and on mountain peaks at the highest elevations. The region of investigation includes the municipios of Allende, Aramberri, Dr. Arroyo, Galeana, Iturbide, Linares, Montemorelos, Rayones, Sabinas Hidalgo, Salinas Victoria, Santa Catarina, Santiago, Villa Aldama, Villa de García and Zaragoza in Nuevo León and Arteaga and Ramos Arizpe in Coahuila, and includes habitats ranging in elevation from 475 to 3700 meters.